Subjectively speaking of French - Smuk, Maciej (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The main objective of the article is to present the results of some research – carried out with students of French philology in Poland – on their representations regarding to the French language. Some of the aspects will be subjected to a detailed analysis: the feelings that French evokes, its social status, the difficulties identified by the students as the most salient in French learning. All the images, woven by future philologists in their individual productions (and therefore subjective par excellence), allow us to reconstruct the semantic fields specific to the French language.